3DN C/SiC composites with different porosities for tunable lubrication performance. Issue 10 (15th May 2021) - Yang, Yubo; Zhao, Yu; Mei, Hui; Chen, Chao; Cheng, Laifei
Abstract: Three-dimensional needled carbon fiber reinforced silicon carbide (3DN C/SiC) composites are potential candidates for lubrication systems because of their great lubrication and wear resistance performance. In this paper, different thicknesses of SiC were deposited by chemical vapor infiltration (CVI) method to prepare 3DN C/SiC composites with controllable porosities, aiming to investigate the effect of different porosities on their lubrication performance under the various load-bearing conditions. Results showed that the friction coefficients of 3DN C/SiC composites decreased with increasing porosity, and the wear rate of the sample with a porosity of 60% was much higher than that of samples with porosity of 30% and 15%. Specifically, the 3DN C/SiC sample with a porosity of 30% exhibited ideal lubricating performance under the load of 10 N, with a lowest friction coefficient of 0.230 and favorable wear rate of 2.20 × 10 −4 mm 3 /(N·m). As for the effect of load, the friction coefficient and wear rate of the sample with a porosity of 30% decreased with increasing load. The lubrication mechanism is mainly the formation of friction film. Therefore, this study presented an effective way to enhance the lubrication performance of 3DN C/SiC composites, which makes it practically applicable in lubrication systems.